2021
DOI: 10.1021/acsearthspacechem.0c00319
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tropical Weather and Northeasterly Air Mass on Carbonaceous Aerosol in the Southern Malay Peninsula

Abstract: Carbonaceous aerosols play a key role in climate modification and exert a deleterious effect on human health. Thus, this study aimed to determine the thermally derived carbonaceous fraction in particulate matter (PM)2.5 from the Southern Malay Peninsula, a tropical area in Malaysia, during January 2019 to March 2019. PM2.5 was captured on quartz filters using a high-volume sampler on a 24 h basis. Eight of the carbon fractions were measured using the thermal optical reflectance method. Carbonaceous aerosol was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…During the northeast monsoon, Fujii et al [64] reported that OC and EC during 2011-2012 in Petaling Jaya, were 5.2 and 3.4 µg/m 3 , respectively. OC and EC were 2.90 and 1.56 µg/m 3 , respectively, during the north-easterly monsoon in 2019 from the urban sites in southern Malaysia [65]. Comparing the OC and EC data reported previously in other cities in Malaysia, the levels of OC and EC were relatively high during the north-easterly monsoon.…”
Section: Oc Ec and Socmentioning
confidence: 47%
See 1 more Smart Citation
“…During the northeast monsoon, Fujii et al [64] reported that OC and EC during 2011-2012 in Petaling Jaya, were 5.2 and 3.4 µg/m 3 , respectively. OC and EC were 2.90 and 1.56 µg/m 3 , respectively, during the north-easterly monsoon in 2019 from the urban sites in southern Malaysia [65]. Comparing the OC and EC data reported previously in other cities in Malaysia, the levels of OC and EC were relatively high during the north-easterly monsoon.…”
Section: Oc Ec and Socmentioning
confidence: 47%
“…The results from this study show that char-EC is about 12 times greater than soot-EC. Soot-EC potentially emits from vehicle combustion and forest fires while char-EC is released from biomass and coal burning sources [65]. Thus, the PM 2.5 is influenced by biomass and coal combustion sources.…”
Section: Oc Ec and Socmentioning
confidence: 99%
“…In addition, an activity that can increase the average carbon monoxide concentration of 23-46 mg/m 3 for 8 hours, such as smoking, emits smoke in vehicles, homes, offices, and restaurants (Whitworth, 2020). Wind conditions greatly affect the spread of pollutants in the air and horizontal transportation (Suradi et al, 2021). The impact of wind generated by industrial emission sources in urban and transportation areas and natural conditions, such as fires are significant for spreading air pollutants (Fan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Variation in CO concentration is determined by not only emission reductions but also meteorological (METRO) conditions . For instance, wind condition greatly affects horizontal transport and dispersion of air pollutants. , The wind impacts are particularly important for the dispersion of air pollutants produced by industrial emission sources in urban areas and the transport of smoke released by natural sources (e.g., wildfire). , Significant wind impacts on the pollutant transport were even found in the Arctic region . Because the CO is less affected by wet scavenging, it has been frequently used as a tracer of other air pollutants to identify the transport efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…7 For instance, wind condition greatly affects horizontal transport and dispersion of air pollutants. 8,9 The wind impacts are particularly important for the dispersion of air pollutants produced by industrial emission sources in urban areas and the transport of smoke released by natural sources (e.g., wildfire). 10,11 Significant wind impacts on the pollutant transport were even found in the Arctic region.…”
Section: ■ Introductionmentioning
confidence: 99%